Depiction of slaves in Django Unchained (2012) in the mould of spaghetti Western and blaxploitation genres / Muhammad Ikhwan Radzali - Radzali, Muhammad Ikhwan (Faculty of Film, Theatre and Animation, 2015)
This thesis analyses the depiction of African-American slaves in writer / director Quentin Tarantino’s Django Unchained (2012), a Western film known for its portrayal of the African-American slave trade era in the mould of Spaghetti Western and Blaxploitation film genres. The topic of this thesis is problematic in a sense that certain audiences and a fellow well-known filmmaker are put off by Tarantino’s sensationalist approach when it comes to dealing with a taboo topic such as African-American slavery through its choice of genres. This dissertation uses the qualitative approach; thus, documents pertaining to the history of African- Americans during the slavery era, the height of Civil Rights Movement, their early post-slavery involvements in Hollywood productions and news articles on an equivalent form of oppression and the latest scenarios for the African-Americans in Hollywood are put to use to gather the appropriate materials that are essential for this study. Additionally, other materials on films about African-American slavery including Django Unchained and the films themselves also help in aiding this interpretation on the slaves in this film. As for the objectives of this research, it aims to delve deeper into the reasoning behind Tarantino’s choice in filming Django Unchained in the Spaghetti Western and Blaxploitation approaches instead of a straightforward drama film and his deliberate adjustments toward his own filmmaking signatures to accommodate the film’s narrative to send a message on the repercussions of racism. The results from these analyses proves that Tarantino indeed never meant to make Django Unchained an accurate representation of the group of slaves in the film, but rather as an alternative take on how do these slaves endure their torture during the slavery era through their own means of survival.